Morphologic Analysis of Cytomegalovirus Infected Cells in Bronchial Washing Cytology: Comparison of Liquid-Based Preparation and Conventional Smear - Jae Yeon Seok; Jungsuk An; Seung Yeon Ha; Dong Hae Chung; Sangho Lee; Hyunchul Kim (Journal of Pathology and Translational Medicine, 2016)
Background: The cytopathic effects of cytomegalovirus (CMV) infection have been well described since the virus was first reported; however, the morphology of CMV infection has not been clearly studied. We examined the difference in detailed cytologic findings in bronchial washing cytology between liquid-based and conventionally prepared smears. Methods: Bronchial washing cytology was processed using either the conventional preparation (CP) or liquid-based preparation (LBP). Sixty-nine cells with typical cytopathic effects of CMV infection were detected on CP slides and 18 cells on LBP slides. Using the image analyzer, area, circumference, major axis, and minor axis of the cytoplasm, nucleus, and intranuclear inclusion were measured in singly scattered CMV-infected cells, and histiocytes were used as a control. Results: The mean cytoplasmic area of CMV-infected cells was 1.47 times larger than that of histiocytes in CP and 2.92 times larger in LBP (p<.05). The mean nuclear area of CMV-infected cells was 2.61 times larger than that of histiocytes in CP and 4.25 times larger in LBP (p<.05). The nucleus to cytoplasm ratio and intranuclear inclusion to cytoplasm ratio of the mean area, circumference, major axis, and minor axis in CP were larger than those in LBP (p<.05). Conclusions: The sizes of cytoplasm, nucleus, and intranuclear inclusion were larger in LBP than in CP, indicating that CMV-infected cells are easily detectable in LBP. However, the nucleus-to-cytoplasm ratio was larger in CP, suggesting that differentiation from malignancy or regenerative atypia requires caution in CP.